2021
DOI: 10.1016/j.lwt.2020.110313
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli K12 in phosphate buffer saline and orange juice by high hydrostatic pressure processing combined with freezing

Abstract: Synergistic action of high hydrostatic pressure (HHP) and freezing on inactivation of Escherichia coli K12 in phosphate buffered saline (PBS) was investigated by employing response surface methodology. Samples containing E. coli K12 were stored at 4, −24 and −80 °C overnight before they were pressurized. A maximum of 1.83 log reduction of CFU•ml -1 was obtained following a 9-min treatment at 400 MPa and 4±1 °C in samples stored at 4 °C whereas, 5.63 and 6.83 log reductions were obtained in samples frozen at −2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…According to Montiel et al [50], the combination of HHP (450 MPa for 5 min) and reuterin (16 mmol/L), lactoperoxidase system (2.8 U/g) or lactoferrin (1 g/L) treatments of cold-smoked salmon results in a 1.8-3.5 log CFU/mL reduction. In addition, Bulut and Karatzas [51] found that the combination of HHP (441 MPa for 5 min) and freezing, at 4 • C and −24 • C, leads to 1.01 and 5.19 log CFU/mL, respectively, which were lower than in our research. Thus, it could be inferred that this new method has a superior bactericidal effect.…”
Section: Discussioncontrasting
confidence: 86%
“…According to Montiel et al [50], the combination of HHP (450 MPa for 5 min) and reuterin (16 mmol/L), lactoperoxidase system (2.8 U/g) or lactoferrin (1 g/L) treatments of cold-smoked salmon results in a 1.8-3.5 log CFU/mL reduction. In addition, Bulut and Karatzas [51] found that the combination of HHP (441 MPa for 5 min) and freezing, at 4 • C and −24 • C, leads to 1.01 and 5.19 log CFU/mL, respectively, which were lower than in our research. Thus, it could be inferred that this new method has a superior bactericidal effect.…”
Section: Discussioncontrasting
confidence: 86%
“…HHP treatment has been proven to be efficient in the inactivation of microbes in a wide range of food products, including processed fruits, meat and meat products, and dairy products, which serve as an excellent medium for microbial growth. The recently published study by Bulut and Karatzas ( 166 ) investigated the effectiveness of HHP against E. coli in liquid food. Orange juice was stored at −80°C, and then HHP treatment was applied to the juice with pressure of 250 MPa for 900 s. The HHP treatment reduced the microbial load by 4.88, 4.15, and 4.61 log CFU/ml for orange juice with pH 3.2, 4.5, and 5.8, respectively.…”
Section: Non-thermal Technologiesmentioning
confidence: 99%
“…Recently, a good synergistic effect on the sterilization of pressure and subzero temperatures was achieved in a special container reported in our previous studies [ 9 , 10 ]. Freezing prior to HP processing achieved better inactivation effect compared with unfrozen samples [ 11 , 12 ]. A 5.63 log reduction was obtained in samples frozen at −24 °C, while only a 1.83 log reduction was obtained in unfrozen samples at 4 °C following a 9 min treatment at 400 MPa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Freezing prior to HP processing achieved better inactivation effect compared with unfrozen samples [ 11 , 12 ]. A 5.63 log reduction was obtained in samples frozen at −24 °C, while only a 1.83 log reduction was obtained in unfrozen samples at 4 °C following a 9 min treatment at 400 MPa [ 11 ]. Further studies are necessary to better understand the influenced factors of the inactivation effect of HP treatment, including frozen phase, pressure levels, application modes, substrates, and recovery medium.…”
Section: Introductionmentioning
confidence: 99%